Nilai Pendidikan Akhlak dalam Novel Pudarnya Pesona Cleopatra Karya Habiburrahman El-Shirazy (Pembelajaran Sastra di Era Merdeka Belajar) - Marwan, Iwan; Adha, Asyrul Hanni (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2022)
This study aims to describe the value of moral education in the novel Pudarnya Pesona Cleopatra by Habiburrahman El-Shirazy (litteratur learning in era merdeka belajar). This research uses a qualitative research type of library research (library research) to get a description in the form of clear words. The method used is descriptive analysis to analyze, identify and examine the novel Pudarnya Pesona Cleopatra by Habiburrahman El-Shirazy related to moral education. The source of this research is the novel Pudarnya Pesona Cleopatra by Habiburrahman El-Shirazy. The data collection technique of this research uses documentation taken from the novel. The data analysis technique uses content analysis, namely by carefully identifying the data that contains elements of moral education, then linking it with the appropriate theory. The results of the study indicate that there are values ​​of moral education in the novel Pudarnya Pesona Cleopatra by Habiburrahman El-Shirazy: (1) The value of moral education to God in the novel includes: Dhikr, which is remembering Allah by mentioning Him in the worst situations and conditions, Praying is asking for God in order to get His goodness and pleasure and Worship is doing all bodily obedience only because of Allah, (2) The value of moral education to fellow humans in the novel includes: Birrul Walidain, namely having character to parents by being devoted to him by obeying and loving him other than that morals to humans also maintain friendship with others and Itsar, namely prioritizing the interests of others over personal interests, (3) The value of moral education to oneself in the novel includes: Trust is something that is entrusted to others in the form of messages carried out well, Patience with exams and trials given o by Allah with grace and fortitude, and maintain self-respect by covering the nakedness and lowering the gaze of the opposite sex who is not a mahram.